FVC, FEV1 and FEV1/FVC% in Patients with Depressive Illness and their Relationships with the level of Depression - Islam, Shausheen; Jahan, Nasim; Sultana, Nayma; Akter, Rezina (Journal of Bangladesh Society of Physiologist, 2011)
Background: Depressive illness is a common psychological disorder which affects various organs including lungs. Many studies have reflected decreased lung functions in patients with depressive illness. Objective: The present study was undertaken to measure some pulmonary function parameters in diagnosed female patients with depressive illness to evaluate their lung functions status. Methods: This cross-sectional study was carried out in the Department of Physiology, SSMC, Mitford, Dhaka, from 1st July 2009 to 30th June 2010 on 30 female patients with depressive illness, age ranged from 20- 40 years. Depressed patients (study group) were divided into patients with minor depressive illness (group-B1) and patients with major depressive illness (group- B2). For comparison, 30 age and BMI matched apparently healthy subjects (control group-A) were also studied. The study groups were selected from the Out Patient Department of Psychiatry, SSMC, Mitford, Dhaka and the control group was selected by personal contact. Pulmonary function parameters like FVC, FEV1, FEV1/FVC%, of all subjects were measured by digital spirometer. Statistical analysis was done by using appropriate method as applicable. Results: All the pulmonary function parameters except FEV1/FVC% were significantly (p<0.001) lower in patients with depressive illness in comparison to those of control. Again, pulmonary function parameters like FVC (p<0.01), FEV1 (p<0.05) showed significant negative correlation with the level of depression in patients with major depressive illness. Conclusion: This study reveals that some pulmonary functions may be reduced in patients with depressive illness especially in major depressive patients which is negatively related with level of depression. Key words: FVC; FEV1; depressive illness. DOI: 10.3329/jbsp.v5i2.6784 J Bangladesh Soc Physiol. 2010 December; 5(2): 94-100